Burial and exhumation history of Jurassic sedimentary rocks in the southern margin of the Junggar Basin: Implications for the growth of the northern Tianshan Mountains. (15th September 2022) - Zhang, Huaihui; Zhang, Zhicheng; Tang, Wenhao; Li, Ke; Li, Jianfeng; Wang, Qi; Ding, Cong
Graphical abstract: Highlights: Apatite fission-track dating yields 147–50 Ma for the Jurassic sedimentary rocks in the southern margin of Junggar Basin. The Jurassic sedimentary rocks experienced two cooling stages at 150–110 Ma and the Late Miocene (20–10 Ma). The exhumation of Jurassic sedimentary rocks was associated with the northward expansion of the Tianshan Mountains. The two cooling stages had a wide range of regional dynamic responses in northwestern China. Abstract: Constraining the burial and exhumation evolution of sedimentary basins is crucial for understanding the deformation histories of basin–mountain transition zones. The thick Jurassic sedimentary successions on the southern margin of the Junggar Basin are an essential archive of the uplift and deformation of the Tianshan Mountains. Apatite fission-track and vitrinite reflectance analyses were performed on the Jurassic sedimentary rocks bordering the northern Tianshan Mountains, providing direct insight into the burial and exhumation of the southern margin of the Junggar Basin. Our apatite fission-track data indicate four main cooling stages during 150–125 Ma; 120–105 Ma; 100–80 Ma; and 75–45 Ma. Thermal-history modeling results demonstrate that the Jurassic sedimentary rocks were exhumed in the northern Tianshan Mountains, indicating a history of probable Early to Middle Jurassic sedimentary burial followed by slow cooling commencing at approximately 150–110 Ma. Then, this region undergone gradual deplanation between the Late Jurassic–Cretaceous and the Miocene and rapid cooling since the Late Miocene (20–10 Ma). These two stages of cooling and exhumation are interpreted to reflect the accretion of the Lhasa Block and the India-Eurasia collision, respectively. Furthermore, the thermal history of the Jurassic sedimentary rocks is consistent with the sedimentation pattern and depositional environments in the southern margin of the Junggar Basin, providing complementary evidence for the time of exhumation and implying that denudation migrated into the Junggar Basin concurrent with uplift of the northern Tianshan Mountains.